Aquaculture farmers’ perceptions of climate-related risks in the Mekong Region - Louis Lebel (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Local studies have shown that aquaculture is impacted by extreme weather events, the risks of which vary seasonally and among years. Less is known about the effects of geographical differences in climate or social organization for how climate-related risks are perceived, as there have been few larger scale studies. This study documents key findings from a large-scale survey of levels of concern and experience with significant losses of over 3300 aquaculture farmers in Cambodia, Laos, Myanmar, Thailand, and Vietnam. Important climate-related risks included rapid changes in temperature, intense rainfall events, and floods. Farmers in Laos were less concerned with risks to profits than those in other countries. Farmers who had experienced significant losses from any climate-related source were more concerned with risks. Women and higher educated farmers perceived higher risks. Those with intensified production systems perceived lower risks and observed fewer climate changes. Perceptions of historical changes in risks and expectations for future risks were often strongly associated with each other and levels of concern, as well as experiences of losses, underlining that risk perception has multiple, inter-related dimensions. Geographical differences in risk perception were related to differences in both physical climate and social factors.